Analisis Kemiskinan di Provinsi D.I Yogyakarta - Ayuni Yosa (Bandung Conference Series: Economics Studies, 2022)
Abstract. Poverty is a serious problem that exists in Indonesia, especially the Province in D.I Yogyakarta. Poverty occurs due to various factors, including the high unemployment rate which is not accompanied by the rate of economic growth itself so that people's welfare arises. This study aims to determine the effect of economic growth, unemployment and poverty lag on poverty in D.I Yogyakarta in 2000-2020. To achieve this goal, an econometric approach is used. The estimation results repeatedly produce information that changes in poverty in D.I Yoyakarta can be explained by the variables of economic growth, open unemployment rate, and poverty lag. The coefficient of the equation provides information that the effect of a 1 percent increase in the economic growth variable has the potential to reduce poverty by 0.680040. In addition, the effect of an increase in the unemployment variable by 1 percent has the potential to reduce poverty by 0.0660675. The effect of the poverty lag gives an opportunity to achieve the poverty reduction target of 0.475096. The results of the hypothesis together that the LPE, TPT, and Lag Poverty variables have a significant effect on the dependent variable, namely Poverty Abstrak. Kemiskinan merupakan permasalahan yang serius yang ada di Indonesia khususnya Provinsi Daerah Istimewa Yogyakarta. Kemiskinan terjadi diakibatkan berbagai faktor termasuk diantaranya disebabkan karena tingkat pengangguran yang tinggi yang tidak dibarengi oleh laju pertumbuhan ekonomi itu sendiri sehingga timbulah ketidaksejahteraan rakyat. Penelitian ini bertujuan untuk menentukan pengaruh dari pertumbuhan ekonomi, pengangguran dan lag kemiskinan terhadap kemiskinan di D.I Yogyakarta tahun 2000-2020. Untuk mencapai tujuan tersebut digunakan pendekatan ekonometrika. Hasil estimasi secara berulang menghasilkan informasi bahwa perubahan kemiskinan di D.I Yoyakarta dapat dijelaskan oleh variabel pertumbuhan ekonomi, tingkat pengangguran terbuka, dan lag kemiskinan. Koefisien Persamaan memberikan informasi bahwa pengaruh kenaikan variabel pertumbuhan ekonomi 1 persen berpotensi untuk menurunkan kemiskinan sebesar 0.680040. Selain itu pengaruh kenaikan variabel pengangguran 1 persen berpotensi untuk menurunkan kemiskinan sebesar 0,0660675. Adapun pengaruh lag kemiskinan memberi peluang tercapainya target penurunan kemiskinan sebesar 0.475096. Hasil hipotesis secara bersama-sama variabel LPE, TPT, Lag Kemiskinan mempunyai pengaruh signifikan terhadap variabel dependen yaitu Kemiskinan.